Description of Chinese Ethnic Culture in The Film â€œTurning Redâ€ - Mona Salwa Amin (Syntax Idea)
The purpose of this study was to find out the picture of ethnic Chinese in the film "Turning Red". Cultural elements are language systems, knowledge systems, kinship systems and social organizations, systems of living equipment and technology, economic or livelihood systems, religious and artistic systems. The film "Turning Red" was used as the subject of this study because it has a cultural background of a Chinese family living in Toronto, Canada. This qualitative research uses content analysis method. Many depictions of Chinese culture are found in this film. Religious elements are the dominating element in this film, followed by other elements except language elements that are not depicted in this film.